2019
DOI: 10.1016/s2589-7500(19)30057-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects and preventability of 2627 patient safety incidents related to health information technology failures: a retrospective analysis of 10 years of incident reporting in England and Wales

Abstract: Background The use of health information technology (IT) is rapidly increasing to support improvements in the delivery of care. Although health IT is delivering huge benefits, new technology can also introduce unique risks. Despite these risks, evidence on the preventability and effects of health IT failures on patients is scarce. In our study we therefore sought to evaluate the preventability and effects of health IT failures by examining patient safety incidents in England and Wales.Methods We designed our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
0
29
0
7
Order By: Relevance
“…Fragmented displays can prevent coherent views of patients' medications, and lead to prescription errors; deaths have been associated with health IT failures, and in Pittsburgh, Pennsylvania, USA a rise in paediatric mortality was coincident with a new system implementation. [27][28][29] Within systems, there is a balance to be struck between the precision of coded data and the value of the precision, while recognising that often precision may be spurious. Data options must be precise enough to enable clinically accurate and safe communication but be easy to navigate for clinicians.…”
Section: Why Does This Matter?mentioning
confidence: 99%
“…Fragmented displays can prevent coherent views of patients' medications, and lead to prescription errors; deaths have been associated with health IT failures, and in Pittsburgh, Pennsylvania, USA a rise in paediatric mortality was coincident with a new system implementation. [27][28][29] Within systems, there is a balance to be struck between the precision of coded data and the value of the precision, while recognising that often precision may be spurious. Data options must be precise enough to enable clinically accurate and safe communication but be easy to navigate for clinicians.…”
Section: Why Does This Matter?mentioning
confidence: 99%
“…The NHS relies on staff from outside of the UK who predominantly work with metric measurements and expect to continue this, but are often confronted with staff using a hybrid approach, which could cause misunderstandings and errors. Martin et al (2019) found that in a decade of retrospective analysis within the UK, there were 2627 health information technology failures that led to safety events. Perhaps similar research is needed to assess any issues linked with measurements and their communication, especially aspects related to the use of imperial measurements alongside accepted metric units.…”
Section: U S a G E G U I D E L I N E Smentioning
confidence: 99%
“…Previous studies have used these data to understand the general effects of health IT on safety and have focused on specific topics, such as usability, downtime, and interoperability. [2][3][4][5][6][7] In The Lancet Digital Health, Guy Martin and colleagues 8 describe one of the largest analyses of health IT safety failures using a database of more than 13 million patient safety-event reports, and provided further evidence for the association between health IT and patient harm. 2627 events were identified as being related to health IT.…”
mentioning
confidence: 99%
“…We discuss these benefits and challenges in the context of understanding health IT safety with a focus on the study by Martin and colleagues. 8 It is important to recognise that identifying health IT-related safety issues, particularly those related to the electronic health record (EHR), can be difficult, given that this technology is now a natural part of the care process and many clinicians might not attribute a safety concern to the EHR or other types of health IT.…”
mentioning
confidence: 99%